Analisis Dampak Motivasi Belanja Hedonis, Price Discount, Kualitas Produk Terhadap Pembelian Impulsif - Nadaa Masicha, Nabilla; Br Sitepu, Sri Nathasya (Gorontalo Management Research, 2024)
This research was conducted to examine and discuss how hedonis shopping motivation, price discount, and product quality can affect impulsive buying at HM Pakuwon Mall Surabaya. This study used quantitative research methods and the sampling technique used in this study was non-probability sampling, namely purposive sampling. This research data collection was distributed to 200 respondents who had made a purchase at HM Pakuwon Mall Surabaya at least once. Data obtained through online questionnaires. The online questionnaire here refers to the google form as a media for administering the questionnaire. The collected data was processed using IBM SPSS Statistics 26 (Statistical Package for Social Science) Software. The analytical tool used in this study is multiple linear regression analysis. The results of this study indicate that hedonic shopping motivation has a prositive and significant effect on impulsive buying at HM Pakuwon Mall Surabaya, price discount have a negative effect and significant effect on impulsive buying at HM Pakuwon Mall Surabaya, and product quality has a positive but not significant effect on impulsive buying at HM Pakuwon Mall Surabaya.